Unions, efficiency wages, and unemployment - Rüdiger Wapler (Eberhard Karls Universität Tübingen, Wirtschaftswissenschaftliche Fakultät, 2001)
This paper develops a dynamic general equilibrium dual labour market model which incorporates both efficiency wages and union bargaining with monopolistically competitive firms. In one sector, a traditional sector produces a homogeneous good and firms face perfect competition on the product market. In the other sector, monopolistically competitive firms produce a horizontally differentiated good. In this sector, unions represent the interests of the workers and through bilateral bargaining with the employers, try to capture some of the rents which accrue here. Further, firms can increase their profits by paying the workers with the highest productivity an efficiency wage. Therefore, there is not only a wage differential between the two sectors, but also within the unionized sector. It is shown that not only the degree of union bargaining power but also the market power firms possess on the product market leads to an increase in unemployment. – – In einem allgemeinem Gleichgewichtsmodell wird ein unvollkommener dualer Arbeitsmarkt, bei dem in einem Sektor sowohl Effizienzlöhne gezahlt werden als auch Gewerkschaften vertreten sind, die das Lohnniveau für Ihre Mitglieder aushandeln, mit monopolistischer Konkurrenz auf dem Gütermarkt kombiniert. Es zeigt sich, dass nicht nur die Verhandlungsmacht der Gewerkschaften, sondern auch Marktmacht der Unternehmen auf dem Gütermarkt die Arbeitslosigkeit erhöhen. Dies liegt darin begründet, dass zum einen ein höherer Wettbewerbsdruck die Lohnforderungen der Gewerkschaften reduziert und zum anderen die Unternehmen nur einen geringeren Preisaufschlag auf ihre Kosten verlangen können. Beide Effekte führen dazu, dass die Preise für diese Güter sinken, wodurch die Güter- und die Arbeitsnachfrage steigen.
urn:nbn:de:bsz:21-opus-19528
Keywords: J41; J42; J51; 330; Arbeitsmarkt; Gewerkschaft; Tarifpartner; Theorie der Arbeitslosigkeit; Arbeitsmarkttheorie; Dualer Arbeitsmarkt; Mehr-Sektoren-Modell; Lohnverhandlungstheorie; Effizienzlohn; Monopolistischer Wettbewerb; Mark-up Pricing; Theorie